Physical work environment satisfaction and productivity of working adults in Malaysia - Kok, Stephanie Sook Munn; Alia Azalea (Penerbit Universiti Kebangsaan Malaysia, 2024)
Studies have established that satisfaction with the physical work environment has an impact on individual productivity. This study investigated the influence of physical work environment satisfaction (including environmental design, welfare facilities, work organization, equipment and tools, and health and safety) on the productivity of Malaysian employees as they gradually return to physical workplaces post-pandemic. A total of 253 working adults (135 males, 118 females, mean age = 39.00 years) participated in this cross-sectional study. The results supported the hypotheses that the physical work environment collectively, and environmental design and tools and equipment specifically, predict employee productivity. These findings emphasize the importance for organizations to consistently maintain satisfaction with the physical work environment in order to enhance employee productivity.